2011
DOI: 10.1155/2011/645820
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of a Biomedical-Grade Bilayer Chitosan Porous Skin Regenerating Template as a Potential Dermal Scaffold in Skin Tissue Engineering

Abstract: Chitosan is a copolymer of N-acetylglucosamine and glucosamine. A bilayer chitosan porous skin regenerating template (CPSRT) has been developed for skin tissue engineering. The pore size of the CPSRT was assessed using a scanning electron microscopy (SEM). The in vitro cytocompatibility of the CPSRT was tested on primary human epidermal keratinocyte (pHEK) cultures by measuring lactate dehydrogenase (LDH) levels and skin irritation by western blot analysis of the interleukin-8 (IL-8) and tumor necrosis factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Porosity on a specific scale accelerates specific tissue integration and vascularization. This can be achieved by using a high density of cells to proliferate throughout the scaffold and to ultimately regenerate the specific tissue [11]. In the area of tissue engineering, the function of a scaffold is actually to provide three-dimensional cultivation conditions and to ultimately enhance cell adhesion and proliferation in vitro [9], [15].…”
Section: K Microstructure Of Chitosan Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porosity on a specific scale accelerates specific tissue integration and vascularization. This can be achieved by using a high density of cells to proliferate throughout the scaffold and to ultimately regenerate the specific tissue [11]. In the area of tissue engineering, the function of a scaffold is actually to provide three-dimensional cultivation conditions and to ultimately enhance cell adhesion and proliferation in vitro [9], [15].…”
Section: K Microstructure Of Chitosan Setsmentioning
confidence: 99%
“…The viability assay of the HFSCs on the chitosan SETs is presented in Table 1; this assay demonstrated that the growth of the HFSCs increased over time. This promising finding of HFSC viability and growth using a chitosan SETs has increased the interest of researchers in employing this scaffold for the fabrication of epidermal substitutes [6], [9], [11]. Chitosan skin substitutes and chitosan SETs have been demonstrated to accelerate wound healing in irradiated rats.…”
Section: Attachment and Proliferation Of Hfscs On Chitosan Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 2 h postculture, another 100 lL of culture medium was added to each chitosan. At 6 h postculture, the chitosan discs were transferred into 24-well plates and medium was added adequately as previously explained 7 followed by incubation under 5% CO 2 at 37°C. The growth medium was changed every day.…”
Section: Three-dimensional Cultures Of Hdfs In Chitosan Skin Templatesmentioning
confidence: 99%
“…Tridimensional porous scaffolds played a crux role in synthetic bone, because the scaffolds could imitate the bone constructions and role of the extracellular matrix and endorse cell conglutination, multiplication, and differentiation. Besides they could transport nutrient and metabolic waste [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%